Symmetry of tetrahydroxycalix[4]arenes - M. GHORBANI; A. R. ASHRAFI; J. SAFAEI-GHOMI; A. GHOLAMI (Journal of the Serbian Chemical Society, 2006)
Graph theory provides an elegant and natural representation of molecular symmetry and the resulting group expressed in terms of permutations is isomorphic to the permutation-inversion group of Longuet-Higgins. In this paper, using the group theory package GAP, the character table and the automorphism group of the Euclidean graph of tetrahydroxycalix[4]arenes were computed.